The Adoption and Effect of Artificial Intelligence on Human Resources Management - Tyagi, Pallavi (Emerald Studies in Finance, Insurance, and Risk Management Series, 2023)
Emerald Studies In Finance, Insurance, And Risk Management 7 explores how AI and Automation enhance the basic functions of human resource management